2016
DOI: 10.1002/elan.201600198
|View full text |Cite
|
Sign up to set email alerts
|

Label‐free, PCR‐free DNA Hybridization Detection of Escherichia coli O157 : H7 Based on Electrochemical Nanobiosensor

Abstract: 1IntroductionFoodborne infections are an important public health concern worldwide. Escherichia coli O157 :H7i saparto ft he enterohemorrhagic group of E. coli (EHEC). Clinical symptoms of patients infected with E. coli O157 :H7h ave aw ide range and diagnosis of the symptoms is difficult. Thep athogen causes diarrhea and hemolytic uremic syndrome (HUS) in human beings.H emolytic uremic syndrome (HUS), al ife threatening complication that causes kidney failure,i sd evelopedb ya bout 10 %o fp atients, mostly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Recent studies, however, concluded that the presence of this gene is not essential to cause a severe illness, showing that not all STEC causing illness outbreaks had this gene present (EFSA Panel on Biological Hazards, 2020). Less often, other virulence factors were used such as the rfbE gene coding for an O-antigen synthesis for O157 serotype, shown in the work of Minaei et al (2016). An ideal STEC detection technique should, however, focus on all serotypes which potentially cause the infection.…”
Section: Stecmentioning
confidence: 99%
“…Recent studies, however, concluded that the presence of this gene is not essential to cause a severe illness, showing that not all STEC causing illness outbreaks had this gene present (EFSA Panel on Biological Hazards, 2020). Less often, other virulence factors were used such as the rfbE gene coding for an O-antigen synthesis for O157 serotype, shown in the work of Minaei et al (2016). An ideal STEC detection technique should, however, focus on all serotypes which potentially cause the infection.…”
Section: Stecmentioning
confidence: 99%
“…Among the different devices developed so far, electrochemical sensors are very advantageous due to their robustness, miniaturization, sensitivity, and fast response along with low-cost/energy/mass characteristics and great potential as PoC devices intended for commercialization. , The working electrode is the core component of any electrochemical sensor, and for DNA sensors, it is where probe ssDNA is immobilized via physical absorption, self-assembly, or covalent bonds (as in the case of thiolated probe ssDNA and Au electrodes). Indeed, the working electrode determines the ultimate properties of the sensor. , Upon hybridization of probe ssDNA with the complementary sequence, an electrochemical signal is generated whose amplitude defines the sensitivity of the sensor . Various electrochemical techniques have been used to enhance the hybridization signal, including voltammetric, amperometric, coulometric, and impedimetric techniques .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the working electrode determines the ultimate properties of the sensor. 13,14 Upon hybridization of probe ssDNA with the complementary sequence, an electrochemical signal is generated whose amplitude defines the sensitivity of the sensor. 9 Various electrochemical techniques have been used to enhance the hybridization signal, including voltammetric, amperometric, coulometric, and impedimetric techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The fast development of microand nanofabricated devices has opened up an exciting realm for the development of a new generation of label-free DNA biosensors. For instance, the label-free detection of E. coli O157:H7 DNA has been reported using piezoelectric sensors and electrochemical biosensors [5,[15][16][17]. More recently, field-effect devices (FEDs) have offered a promising direct electrical readout for label-free DNA detection [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%